Creative nonfiction in sport and exercise research - Cavallerio, Francesca (New York, NY : Routledge, 2022)
Academics around the world recognise the effectiveness of storytelling as a way to engage audiences in conversations, raising awareness of issues, and encouraging change. Stories are now seen as the best medium to convey information to diverse audiences. This book explores a novel approach to representing research findings through the adoption of creative nonfictional stories (CNF). At a time when dissemination of scientific research is constantly highlighted as a fundamental aspect for academics, CNF represents an opportunity to effectively communicate science to non-academic audiences through stories. By providing practical examples of how to transform findings into compelling stories rooted in data, following the mantra of showing rather than telling, which characterises CNF, Creative Nonfiction in Sport and Exercise Research helps researchers - qualitative, quantitative, established professors, and students - to turn their research into stories. A unique contribution to the field, this book is the first in the sport and exercise research field to take scholars on a discovery jouney, moving from their classic realist to a more creative,compelling, but still rigorous representation of research findings. The book features chapters written by authors from different sport research backgrounds, who present the findings of a previously published classic' study rewritten in the form of a story. Reflective chapters focusing on the how-to and the challenges of this creative analytical practice complete the work, to support scholars in developing their creative skills.
Keywords: Exercise -- Research; Sports -- Research; Creative nonfiction; SPORTS & RECREATION / Sports Psychology; EDUCATION / Physical Education